Velocity‐Porosity Relations in Carbonate and Siliciclastic Subduction Zone Input Materials. (28th December 2021) - Jeppson, Tamara N.; Kitajima, Hiroko
Abstract: The mechanical, physical, and frictional properties of incoming materials play an important role in subduction zone structure and slip behavior because these properties influence the strength of the accretionary wedge and megathrust plate boundary faults. Incoming sediment sections often show an increase in compressional wave speed (Vp ) and a decrease in porosity with depth due to consolidation. These relations allow seismic‐velocity models to be used to elucidate properties and conditions at depth. However, variations in these properties are controlled by lithology and composition as well as cementation and diagenesis. We present an analysis of shipboard measurements of Vp and porosity on incoming sediment cores from International Ocean Discovery Program (IODP) expeditions at the Hikurangi Margin, Nankai Trough, Aleutian Trench, Middle America Trench, and Sunda Trench. Porosity for these samples ranges from 5% to 85% and Vp ranges from 1.5 to 6 km/s. Vp ‐porosity relations developed by Erikson & Jarrad (1998), https://doi.org/10.1029/98JB02128 and Hoffman & Tobin (2004) https://10.2973/odp.proc.sr.190196.355.2004, with a critical porosity of ∼30%, can represent carbonate‐poor (<50 wt% CaCO3 ), mainly hemipelagic, incoming sediment regardless of the margin. But these relations tend to underestimate porosity in incoming sediments with carbonate content greater than 50 wt%, which appear to have a critical porosity of between 45% and 50%. This discrepancy will lead to inaccuracy in estimates of fluid budget and overpressure in subduction zones. The velocity‐porosity relation in carbonate sediments is non‐unique due to the complexity that results from the greater susceptibility of carbonate rocks to diagenetic processes. Key Points: Velocity‐porosity relations for siliciclastic subduction zone input sediments are well‐described by existing models Carbonate sediments deviate from current velocity‐porosity models due to diagenetic alteration A preliminary model describing the range of velocities and porosities in both siliciclastic and carbonate sediments is proposed